Impact of chronic obstructive pulmonary diseases on static and dynamic balance - Hayam A. Hussien Abd Allah; Akram Abdelaziz Sayed; Alaa Rashad Mahmoud; Yasser Ramzy Lasheen; Saif Mehmed (Здоров’я, спорт, реабілітація)
Background and purpose